THE DIGITAL MEDIA AND THE MORAL REPRESENTATION OF THE SOCCER ATHLETE - Moioli, Altair; Machado, Afonso Antonio [UNESP] (Univ Illes Balears, 2018)
The aim of this research was to analyze the moral perception of adolescent soccer athletes in virtual and concrete territories. In this qualitative study the data was collected through semi-structured interviews on Facebook, with 14 male athletes, aged between 16 to 18 years (+/- 17.35) who played soccer in official tournaments. After being treated by the Thematic and Discourse Analysis, the data indicated the configuration of a modular man for three different territories: everyday, sporty and virtual environments which leave marks on the moral perception of the young athlete. Athletes believe they are immune from permanent moral values as they move through inter-territorial gaps. Their actions assume the characteristics of a relative moral game, transitory and disconnected from concrete historical parameters, which makes it impossible to realize the intrinsic relationship between the practical dimension and the moral dimension. This research showed the composition of a man / athlete, labeled for each environment that he acts in, a young man shaped in three-dimensional and transient moral.
Keywords: New Technologies; Morality; Soccer; Adolescent; Facebook